Modern methods in human resources management and impact on employee performance (Global Scientific Review, 2024)
The importance of impact of human resources management (Transformational Change-TC, Incremental Change-IC, Expertise-EX) on the dimensions of employee performance (Procedural-PR, Distributive-DI). Here is the necessity of using the system of joint cooperation between employees by identifying the gaps in the delay in developing services for employees of the Central Bank of Iraq. The questionnaire number was 95, 88 were obtained by quantitative distribution and 7 were invalid by using the SPSS statistical program. The number of hypotheses was 6 and all were positive. The researcher was able to achieve the required results and the hypotheses were positive and supportive of developing the performance that everyone calls for achieving. The researcher also focused on continuous follow-up of organizations by following the latest methods in their work